Investigation of the Mechanical Behavior of Laminated Composites Gypsum-Based Plastic Sack Waste Fiber - Indra Mawardi; Samsul Bahri; Hamdani Nurdin; Irwin Syahri Cebro; Luthfi Luthfi; Zuhaimi Zuhaimi; Ismi Amalia (Politeknik Negeri Lhokseumawe, 2023)
The existence of plastic waste, such as used plastic sacks in large quantities, is a crucial problem for the environment and health because of its very low biodegradability. Therefore, reusing plastic sack waste as reinforcement in gypsum composites is a major research issue. This study investigates the mechanical and physical properties of gypsum composites reinforced with fiber layers from plastic sack waste. Gypsum composites are produced using casting gypsum flour as the matrix and various fiber layers from plastic sack waste (1, 2, 3, 4) as reinforcement. Gypsum-based laminated composites were tested for density, flexural strength, and compression. The behavior of mechanical, physical, and damage properties is studied to see its suitability as a building material. The results showed that gypsum composites' density decreased with increasing sack fiber layers. The density of gypsum composites ranges from 1064-1199 kg/m3, with a maximum value in samples with 100% gypsum. The flexural strength of gypsum composites ranges from 2.21-4.10 MPa, and the compressive strength ranges from 3.5-6.66 MPa. Increasing the number of layers of plastic sack fibers reduces density, flexural strength, and compressive strength. However, all the mechanical properties of gypsum composites met the requirements of the EN 13279-2 standard. Failure of fiber delamination with the resulting matrix is the main cause of the decrease in mechanical strength